2024
DOI: 10.1038/s41392-023-01679-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular zinc metabolism and zinc signaling: from biological functions to diseases and therapeutic targets

Bonan Chen,
Peiyao Yu,
Wai Nok Chan
et al.

Abstract: Zinc metabolism at the cellular level is critical for many biological processes in the body. A key observation is the disruption of cellular homeostasis, often coinciding with disease progression. As an essential factor in maintaining cellular equilibrium, cellular zinc has been increasingly spotlighted in the context of disease development. Extensive research suggests zinc’s involvement in promoting malignancy and invasion in cancer cells, despite its low tissue concentration. This has led to a growing body o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 695 publications
(828 reference statements)
0
8
0
Order By: Relevance
“…The MT-zinc axis is closely associated with immune regulation in infectious diseases or atopies [29,39,40]. MT1 and MT2 are two major MTs involved in immune function [35]; however, the distinct roles of MT1 and MT2 have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The MT-zinc axis is closely associated with immune regulation in infectious diseases or atopies [29,39,40]. MT1 and MT2 are two major MTs involved in immune function [35]; however, the distinct roles of MT1 and MT2 have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…MT3 is a Zn-binding protein that can bind up to seven Zn 2+ , and is involved in maintaining intracellular Zn 2+ homeostasis 16 , 53 . Our results demonstrated that under hypoxia treatment, MT3 knockdown reduced intracellular Zn 2+ levels and exogenous Zn 2+ supplementation largely reversed the inhibitory effects of MT3 knockdown on PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc functions with calcium and iron enhancing site specific activities regulating plasma membrane and endosome receptors, effecting virus entry such as SARS-CoV-2. 204 Metallopeptidases can either be derived from microbes or host cells. Human zinc metallopeptidases support immune resistance, controlling inflammation including antigen recognition, processing and ultimately clearance of SARS-CoV-2.…”
Section: Bacterial and Viral Oral Pathogen Persistence In Oral Epithe...mentioning
confidence: 99%